Sheep and Goats nasal Myiasis by Oestrus Ovis in the Sulaimani Province of Kurdistan Region-Iraq - Shareef, Jalal M. (Sulaimani Journal for Pure and Applied Sciences, 2001)
The heads of 2897 sheep, 1006 goats, and 1827 cattle from the local abattoir (Sulaimani-Kurdistan-Iraq were examined for larvae of Oestrus ovis in January to December 1999. The larvae were diagnosed morphologically under a dissecting microscope, and were measured and preserved in 10% formal saline. The prevalence of 0.ovis in sheep was 20.96% and in goats was 13.6 per cent. The monthly infestation rate for sheep varied from 5.06% in March to 56.12% in September, but in goats varied from 2% in February to 66.6% in March. Up to 13 and 6 larvae were collected from individual sheep and goats consecutively. The mean larval burden per sheep and goat positive case over the year was 1.98 and 1.40 respectively. Different size and color of 0.ovis larvae per single animal were observed throughout the year, which might be due to the presence of more than one generation of 0.ovis adult fly in the region or due to rotation of animals in different areas or pastures during transportation and marketing. 0.ovis larvae were present in sheep and goats 12 and 10 months successively per year. In the present study 0.ovis larvae were not found in the heads of cattle. Since this parasite is produce one of the important anthropozoonotic diseases which effects both man and animals, surveillance and monitoring of larval infection have been recommended in order to establish seasonal incidence of 0. ovis infestation and predicting it's outbreaks in the region, to protect man and animals.
Keywords: 0ovis; parasitology,sheep